Multidetector CT of pulmonary cavitation: filling in the holes. Issue 4 (April 2015) - Mortensen, K.H.; Babar, J.L.; Balan, A.
<x xml:space="preserve">Abstract</x> Pulmonary cavitation causes significant morbidity and mortality. Early diagnosis of the presence and aetiology of a cavity is therefore crucial in order to avoid further demise in both the localized pulmonary and systemic disorders that may manifest with pulmonary cavity formation. Multidetector CT has become the principal diagnostic technique for detecting pulmonary cavitation and its complications. This review provides an overview of the aetiologies and their imaging findings using this technique. Combining a literature review with case illustration, a synopsis of the different imaging features and constellations is provided, which may suggest a particular cause and aid the differentiation from diseases with similar findings.